Beyond Trial and Error: Hybrid Strategies and Experiential Learning in Digital Marketing Adoption among Culinary MSMEs in Makassar - Isma Azis Riu (PT Maju Malaqbi Makkarana, 2026)
This study investigates the digital marketing adoption process among local culinary Micro, Small, and Medium Enterprises (MSMEs) in Makassar, Indonesia. Integrating the Technology Acceptance Model (TAM) and Entrepreneurial Learning theory, this research explores how culinary businesses across three distinct segments, traditional culinary warungs, home-based micro-businesses, and lifestyle cafes, navigate digital transformation under resource constraints. Utilizing a qualitative approach involving semi-structured interviews, participant observation, and thematic analysis with 15–20 informants, the study reveals that digital adoption is non-linear, driven by urgent survival needs, and heavily sustained by informal peer-to-peer knowledge sharing. Findings demonstrate that while perceived usefulness drives initial platform trial, entrepreneurial learning and hybrid (online-to-offline) marketing strategies are crucial for long-term competitiveness. The study offers practical, actionable managerial guidelines for business owners to optimize their digital presence and overcome algorithmic dependencies.